Função física, antropometria e saúde relatada de idosos - Moreira, Aparecida Maria (2020)
The present study evaluated and investigated the association of physical function, anthropometric measures and health status reported by the elderly. This study represents a database of the Study of the Fragility of Elderly Brazilians (FIBRA) in Cuiabá, consisting of 387 elderly men and women. An evaluation of the sociodemographic profile, health and level of physical activity was carried out, in addition to body composition by anthropometry using body mass (kg) and height (m), and later calculation of body mass index (BMI) and body circumferences ( abdomen (AC), hip (CQ), waist (CC) and calf (CP). Also, equations were used to estimate the percentage of fat (PG). Physical performance was assessed by handgrip strength tests (FPP ) and Timed Up and Go (TUG) and the relative strength was also calculated (FPP / BMI). For statistical analysis, data normality was verified using the Kolmogorov – Smirnov test and graphical analysis. groups (performance below and above the median in the variables FPP, FPP / BMI and TUG) were assessed by Student's t test for independent samples, while the χ2 test was used to investigate differences in categorical variables. significance of p <0.05. As a result, FPP was positively associated with CP and FPP / BMI negatively with CA and PG of both sexes. TUG was negatively associated with BMI, AC and PG in women and positively associated with CP in men. In women, FPP was associated with BMI, FPP / BMI with hospitalization and PG and TUG associated with arthritis and PG. In men, FPP / BMI was associated with hypertension, arthritis and PG, whereas TUG was associated with diabetes and lung disease. Thus, we concluded that elderly people who had better performance indexes had better body composition and less association with chronic non-communicable diseases regardless of gender. In addition, relative strength (FPP / BMI) proved to be an important marker of performance, being more sensitive than absolute FPP in associating with better body composition, measures and indexes.